Thermal stability of rhombohedral α- and monoclinic β-Ga2O3 grown on sapphire by liquid-injection MOCVD. (15th March 2023) - Gucmann, Filip; Nádaždy, Peter; Hušeková, Kristína; Dobročka, Edmund; Priesol, Juraj; Egyenes, Fridrich; Šatka, Alexander; Rosová, Alica; Ťapajna, Milan
Abstract: We investigate the thermal stability of single-phase undoped epitaxial rhombohedral α- and bi-axially-symmetric, monoclinic β-Ga2 O3 thin films grown on sapphire substrates by liquid-injection metalorganic chemical vapor deposition (LI-MOCVD) by means of in-situ high-temperature X-ray diffraction (HT-XRD) and room temperature (RT) cathodoluminescence (CL). Ga2 O3 layers were vacuum annealed up to 1100 °C, while monitoring the respective 30 3 ‾ 0 and 6 ‾ 03 reflections of α- and β-phase Ga2 O3 . α-Ga2 O3 layers were found to withstand the vacuum annealing at 700 °C/20 min, 750 °C/10 min, and 800 °C/8 min without notable degradation, however an indication of reversible biaxial in-plane compressive strain was observed for annealing temperatures close to 800 °C. Annealing at temperatures above 825 °C led to complete layer degradation and partial phase transformation to ( 010 ) β-Ga2 O3 . β-Ga2 O3 layers showed no notable degradation or structural changes after the annealing at 1100 °C/30 min, however an indication of reversible biaxial in-plane tensile strain was observed for prolonged annealing at 1100 °C. RT CL spectra revealed the Ga2 O3 emission consisted of several distinctive luminescence bands (red, green, blue, and two UV bands). Relatively weak but distinctive signal maxima with energy close to the expected bandgap energies of α- and β-Ga2 O3, at 5.3 and 5.0 eV, respectively, were observed and attributed to their near band-edge (NBE) emissions. Graphical abstract: Image 1